Patient preferences for treatment attributes in moderate-to-severe atopic dermatitis: a discrete choice experiment - Steven R. Feldman; Annie Guerin; Marjolaine Gauthier-Loiselle; Ami J. Claxton; Nisha C. Hazra; Yan Meng; Kirsten Gallant; Sanjeev Balu (Taylor & Francis Group, 2024)
AbstractPurpose: Evidence on treatment preferences of patients with moderate-to-severe atopic dermatitis (AD) in the United States (US) is limited and an assessment of treatment preferences in this group is warranted.Materials and methods: An online discrete choice experiment survey was conducted (June 2023) among US adults with self-reported moderate-to-severe AD or experience with systemic therapy who had inadequate response to topical treatments. Preference weights estimated from conditional logistic regression models were used to calculate willingness to trade off and attributes' relative importance (RI).Results: Participants (N = 300; mean age: 45 years; 70% females; 52% systemic therapy experienced) preferred treatments with higher efficacy, lower risk of adverse events (AEs), and less frequent blood tests (p < .05). Treatment attributes, from high to low RI, were itch control (38%), risk of cancer (23%), risk of respiratory infections (18%), risk of heart problems (11%), sustained improvement in skin appearance (5%), blood test frequency (3%), and frequency and mode of administration (2%); together, AE attributes accounted for more than half of the RI.Conclusions: Participants preferred AD treatments that maximize itch control while minimizing AE risks, whereas mode of administration had little impact on preferences. Understanding patients' preferences may help improve shared decision-making, potentially leading to enhanced patient satisfaction with treatment, increased engagement, and better clinical outcomes.